Acaulidae Fraser 1924 - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
Family Acaulidae Fraser, 1924b Αcaulidae Fraser, 1924b: 173. Current status. Valid. Remarks. Stimpson (1853) described and illustrated Acaulis primarius , a remarkable new genus and species of solitary hydroid from Grand Manan Island, New Brunswick, Atlantic Canada. His polyp was unusual in having a very short, spike-shaped hydrocaulus beneath a large hydranth having scattered capitate tentacles and an irregular whorl of filiform tentacles at the base. Some early authors (e.g., Allman 1872) believed Stimpson’s hydroid constituted a hydranth that had detached from its stalk. Even though G.O. Sars (1874) subsequently described and accurately illustrated A. primarius from Lofoten, Norway, uncertainty persisted over the morphological structure of the species (e.g., Fewkes 1890; Dendy 1902; Fraser 1918c). Fraser (1924b) confirmed the morphology of its hydrocaulus, and established the family Acaulidae to accommodate the species. The taxonomy of A. primarius has recently been reviewed by Schuchert (2006). As noted therein, two species were mistakenly included under that binomen by Stimpson (1853). However, Schuchert concluded that Allman (1872), in effect, had designated a lectotype (ICZN 74.5) by fixing its identity in conformity with that matching the longstanding concept of the species. That concept accords with the only illustration of A. primarius provided by Stimpson (1853, pl. 1, fig. 4). Type material of the species exists at the MCZ (Invertebrate Zoology Coel-162). Published as part of Calder, Dale R. & Choong, Henry H. C., 2018, Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions, pp. 1-83 in Zootaxa 4487 (1) on page 21, DOI:10.11646/zootaxa.4487.1.1, http://zenodo.org/record/1456161